The relationship between socioeconomic factors with fertility rate in Malaysia / Ahmad Muadz Bin Zulqarnain and Mazlynda Md Yusuf - Zulqarnain, Ahmad Muadz; Md Yusuf, Mazlynda (Universiti Teknologi MARA, 2022)
The issue of an ageing population is on the rise globally, and Malaysia is not excluded from facing this issue. Past literature has recognized that the declining fertility rate is one of the main factors that lead to this problem. However, along with the declining fertility rate in Malaysia over time, there are also changes in social and economic factors such as increment in female labor participation, higher house income and consumption expenditure, increasing inflation and changes in the demographic of the population. The study has become a concern since these factors could affect the declining fertility rate. Hence, this study is conducted (1) to analyze the significant socioeconomic factors that affected fertility rate decline in Malaysia; (2) to investigate the short-run and long-run relationship between socioeconomic factors and fertility rates in Malaysia; and (3) to determine the direction of the causal relationship between each of the socioeconomic factors and fertility rates in Malaysia. The Autoregressive Distributed Lag (ARDL) model was conducted for the first and second objectives, while the Granger Causality test was conducted for the third objective. The research is conducted to investigate the stated relationship between the period in the year 1982 to 2019. It can be concluded that income, household consumption expenditure and the female labor force are related to fertility in the short and long run. At the same time, inflation and population ethnicity are only related in the long run.